Economics and Ageing Volume III: Long-term Care and Finance - Iparraguirre, José Luis.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This upper level textbook provides a coherent introduction to the economic implications of individual and population ageing. Placing economic considerations into a wider social sciences context, this is ideal reading not only for advanced undergraduate and masters students in health economics and economics of ageing, but policy makers, professionals and practitioners in gerontology, sociology, health-related sciences, and social care. This volume introduces topics in labour economics, including the economic implications of ageing workforces. It covers pension economics and pension systems with their macroeconomic and distributive effects, and the question of risk. Finally, it describes macroeconomic consequences of ageing populations on aggregate saving, inflation, international trade, and financial markets.
1. The Older Labour Force -- 2. Chronological Age and Labour Productivity -- 3. Age Discrimination and Stereotypes -- 4. Pensions and Pension Schemes -- 5. Macroeconomic Aspects -- 6. Distributive and Actuarial Elements -- 6. Pensions and Risk -- 7. Ageing and -- 8. Economic Growth and Development -- 9. Other Macroeconomic Implications of Populations Ageing .
Keywords: elektronické knihy; electronic books; Medical economics; Aging; Evolutionary economics; Institutional economics; Finance, Public; Population -- Economic aspects; Labor economics; Health Economics; Ageing; Institutional and Evolutionary Economics; Public Economics; Population Economics; Labor Economics